TRM Strengthening of Historic Masonry Vaults Evaluation of use in the Church of Saint Bassiano in Italy and possibilities for Skörstorp’s Church in Sweden - Skeppstedt, Annie (My University)
There is a growing need for reliable, minimally invasive methods to strengthen older buildings such as historic masonry structures, yet limited data exist on the long-term, real-world performance of such interventions. In this thesis the effectiveness of Textile Reinforced Mortar (TRM) in stabilizing historic masonry vaults is investigated through the case study of the Church of Saint Bassiano in Italy, where TRM was applied to the extrados of the vaults in the main nave over a decade ago. This is then applied to a Swedish context through the case study of Skörstorps’s Church; a Swedish round church with similar structural concerns. The goal is to assess the effectiveness of the TRM application in St. Bassiano and evaluate if it is a suitable intervention for the case of Skörstorp’s Church. In St. Bassiano, documentation and visual surveys indicate that TRM effectively stabilized the main nave vaults. However, cracking has since appeared in unstrengthened areas, such as the side aisles and vertical supports, suggesting a redistribution of stress due to localized stiffening. In the Swedish church, long-term cracking has persisted despite earlier repair efforts. Recently, cracks have worsened. The issues appear to have been affected by continuing soil settlement in combination with irregular load from roof and an increased outward thrust from the vaults resulting in increased damage to the round perimeter walls. A preliminary suggested solution informed by the observed hinge settlement mechanism would be to first strengthen the vault with TRM. Should the damage persist, further intervention might be necessary targeting the foundation.
Keywords: Textile Reinforced Mortar, Historic Masonry, Vault Strengthening, Heritage Conservation, Structural Assessment, Case Study I